Goals of Education: Protecting and Promoting Divergence and Sustainability - Parajuli, Mahesh Nath (Journal of Education and Research, 2014)
DOI: http://dx.doi.org/10.3126/jer.v4i1.10709Journal of Education and Research, March 2014, Vol. 4, No. 1, pp. 1-5